The mediating role of narcissistic behavior in the relationship between materialistic orientation and conspicuous online consumption behavior on social media - Sularsih Anggarawati; Armelly Armelly; Muhartini Salim; Wida Odilawati; Fachri Eka Saputra; Ferry Tema Atmaja (Cogent Business & Management, 2023)
Materialism is a prevalent phenomenon in contemporary society and exerts a substantial influence on consumer behavior. Materialistic individuals prioritize their life goals, success criteria, and sources of happiness through the accumulation of wealth, often exhibiting a proclivity towards narcissism. Concurrently, conspicuous consumption entails the consumption of products or services primarily to fulfill social needs. These three facets-materialism, narcissistic behavior, and conspicuous consumption on social media-have garnered significant attention in academic research. However, prior investigations have not delved into the role of narcissistic behavior in elucidating the positive association between materialism and conspicuous consumption on social media. To address this gap, this study employed an online survey method, involving 330 respondents, with 292 questionnaires deemed suitable for analysis. The structural equation model analysis unveiled several noteworthy findings. Firstly, materialistic orientation exhibited a positive and significant impact on both narcissistic behavior and conspicuous consumption on social media. Secondly, narcissistic behavior demonstrated a positive influence on conspicuous consumption on social media. Finally, this study confirmed that narcissistic behavior mediates the positive relationship between materialism and conspicuous consumption on social media. As a result, this study constitutes a valuable contribution to the literature on consumer behavior.
Keywords: 650; conspicuous consumption; Indonesia; materialistic orientation; narcissistic behavior; social media; structural equation model